2014
DOI: 10.1111/cpr.12095
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the multifaceted roles of Atg proteins to improve cancer therapy

Abstract: Autophagy follows a lysosomal degradation pathway in which a cell digests its own components. It is highly regulated by a limited number of autophagy-related genes (Atg) and the proteins they encode, that are crucial for cells to undergo the process via modulating autophagsome formation. Recently, accumulating evidence has revealed the core molecular machinery of autophagy; however, intricate relationships between autophagy and cancer remain an enigma. Several studies have shown that Atgs can play an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Autophagy is another pathway of programmed cell death that permits cells to recycle cytoplasmic components while removing dysfunctional organelles for tissue remodeling [ 30 , 34 , 43 – 45 ]. Of the three categories for autophagy, microautophagy employs the invagination of lysosomal membranes for the sequestration and digestion of cytoplasmic components [ 34 ].…”
Section: Oxidative Stress Cellular Survival and Programmed Cell mentioning
confidence: 99%
“…Autophagy is another pathway of programmed cell death that permits cells to recycle cytoplasmic components while removing dysfunctional organelles for tissue remodeling [ 30 , 34 , 43 – 45 ]. Of the three categories for autophagy, microautophagy employs the invagination of lysosomal membranes for the sequestration and digestion of cytoplasmic components [ 34 ].…”
Section: Oxidative Stress Cellular Survival and Programmed Cell mentioning
confidence: 99%
“…There exist at least 33 autophagic related genes ( Atg ) that have been identified in yeast with TOR and can affect metabolic disorders, cardiovascular disease, cancer and neurodegenerative disease . Atg1, Atg13 (also known as Apg13), and Atg17 are tied to the PI 3‐K, Akt and TOR pathways.…”
Section: Mtor Pathways Of Apoptosis and Autophagymentioning
confidence: 99%
“…In contrast, de‐phosphorylation of Atg13 that can occur during starvation and reduced mTOR activity results in the activation of Atg1 and the induction of autophagy. In mammals, several ULK isoforms exist . The homologues of Atg1 are UNC‐51 like kinase one (ULK1) and ULK2 .…”
Section: Mtor Pathways Of Apoptosis and Autophagymentioning
confidence: 99%
“…Among its related pathways are autophagy pathway and senescence and autophagy in cancer. A recent study has shown that ATG14, a crucial member of ATG gene family, plays a vital role in autophagy processes, [15] which provides protections to cancer cells from the deadly stresses that result from radiation, chemotherapy or other treatments [16]. However, how cancer cells modulate the expression of ATG to prevent cell death caused by radiation and chemotherapy still needs to be discussed.…”
Section: Introductionmentioning
confidence: 99%